Pelatihan Pengemasan dan Labeling Produk untuk Meningkatkan Kemampuan Manajemen Pemasaran bagi UKM Kale Cookies - Menik Aryani; Baiq Herdina Septika; Tama Krisnahadi; Ridho Rafqi Ilhamalimy; Supratman Supratman (Jurnal Pengabdian UNDIKMA, 2022)
This Community Service aims to improve marketing management skills for SMEs Kale Cookies through training on product packaging and labeling according to SNI standards. The partner of this activity is UKM Kale Cookies, which consists of 10 people and has a strong desire to learn packaging management and product labeling. The method of implementing this activity includes training, mentoring, monitoring and evaluation. The result of this service activity is that partners have understood the importance of making creative product packaging and labeling in accordance with SNI standards. In addition, partners also have skills in making product packaging and labels in accordance with SNI standards.